An investigation into the microbial infestation of poultry feeds (Journal of the Bangladesh Agricultural University, 2016)
The Experiments were carried out during the period of July 2001 to December 2002. Infestation of poultry feeds by fungi and aflatoxins content in feeds were determined. Ten feed samples were collected from ten different farms located in three different areas of Bangladesh. Five different fungal species belonging four genera were detected which were Aspergillus flavus, Aspergillus niger, Fusarium spp, Rhizopus stolonifer and Penicillium spp. Among them Aspergillus flavus and Aspergillus niger were found in all the feed samples and the rest were occasionally found. Effect of storage and moisture content of feeds were studied for determining the influence on occurrence of fungal flora in feeds. Higher the storing period of feed along with higher moisture content resulted superior incidences of fungal population in stored feeds. Studied on storage practice with 4 duration of F1 sample revealed that the presence of aflatoxins were 30.52ppb, 33.36ppb, 37.32ppb and 48.35ppb of 5, 10, 15 and 20 days after production of feeds, respectively.J. Bangladesh Agril. Univ. 13(1): 79-86, June 2015